2019
DOI: 10.1016/j.matbio.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix contribution to skin wound re-epithelialization

Abstract: The ability of skin to act as a barrier is primarily determined by cells that maintain the continuity and integrity of skin and restore it after injury. Cutaneous wound healing in adult mammals is a complex multi-step process that involves overlapping stages of blood clot formation, inflammation, re-epithelialization, granulation tissue formation, neovascularization, and remodeling. Under favorable conditions, epidermal regeneration begins within hours after injury and takes several days until the epithelial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
202
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(206 citation statements)
references
References 180 publications
2
202
0
2
Order By: Relevance
“…This underscores that rearranging laminins into fibrous structures via traction stresses is a fundamentally important feature of tissue organization. Similar phenomena might occur in vivo , since extracellular spaces where vasculogenesis takes place during development (35, 36), or angiogenesis during tissue regeneration (37) are generally rich in laminin.…”
Section: Discussionmentioning
confidence: 74%
“…This underscores that rearranging laminins into fibrous structures via traction stresses is a fundamentally important feature of tissue organization. Similar phenomena might occur in vivo , since extracellular spaces where vasculogenesis takes place during development (35, 36), or angiogenesis during tissue regeneration (37) are generally rich in laminin.…”
Section: Discussionmentioning
confidence: 74%
“…Numerous investigations have shown that reepithelialization is necessary for restoration of the epidermis during the burn wound healing (Rousselle, Montmasson, & Garnier, ). Our results showed that ECSs exert important functions in promoting reepithelialization during this process.…”
Section: Discussionmentioning
confidence: 99%
“…The blister plane induced by alkylating agents such as SM coincides precisely with the histological location of laminin‐332 (LM‐332). In normal healthy skin, basal keratinocytes adhere to the basement membrane and the underlying dermis by stable anchoring complexes (made of type VII collagen) attached to anchoring filaments composed of LM‐332 (Marinkovich et al, 1993; Rousselle et al, 1997, 2019; Brittingham et al, 2006; Marinkovich, 2008; Rousselle and Beck, 2013). LM‐332 is a glycoprotein made up of three polypeptide chains (α3, β3, and γ2) that are distinct gene products (see Fig.…”
Section: Figurementioning
confidence: 99%